A New Age for Quercus spp. Fruits: Review on Nutritional and Phytochemical Composition and Related Biological Activities of Acorns - Vinha, A.F. (2018)
The current global food system must adapt to the expected growth of world population (about 9 billion individuals by 2050). This adaptation will probably include an increased consumption of edible wild foods, due to their richness in micronutrients and bioactive compounds, besides providing a cost-effective and sustainable way of improving caloric food security. A striking example of such natural matrices is the Quercus genus, which has the additional advantage of being widespread throughout the Northern Hemisphere. In a traditional sense, Quercus fruits (acorns) were mainly used in animal feeding, despite their potentially important role on the rural economy. But this preconception is changing. In fact, their nutritional value, high contents in phytochemical compounds, biological activity (such as antioxidant, anticarcinogenic, and cardioprotective properties) and use in the treatment of specific diseases (such as atherosclerosis, diabetes, or Alzheimer's disease) have raised the interest in integrating acorns into the human diet. Accordingly, this comprehensive overview was designed to provide an evidence-based review of the literature, with the objective to achieve useful conclusions regarding the nutritional properties, methodologies of extraction, identification, and characterization of a wide variety of bioactive compounds and scientifically validated bioactivities in Quercus species worldwide. The industrial by-products from acorn oil extraction or flour production are also included. Data regarding the analytical techniques, individual compounds, and their bioactivities, are organized in tables. The reported data are discussed and directions for further investigations are suggested, highlighting the use of acorns in food, nutraceutical, and pharmaceutical applications.